A cross sectional study to assess the satisfaction level among people living with HIV/AIDS in a hilly state of northern India - ., Sunita; Dhadwal, D. S.; Gupta, Anmol; Mahajan, Anjali; Sachdeva, Amit (International Journal Of Community Medicine And Public Health, 2018)
Background: Patient satisfaction is the patient’s perception of care received compared with the care expected.Measurement of patient satisfaction helps in understanding patients’ experiences of health care, identifying problems and evaluation of health care. Increased patient satisfaction leads to increased patient retention and decreases medical malpractice claims. Dissatisfied patients may have worse outcomes as they may not follow treatment plans. The objective of the study was to determine the satisfaction level among people living with HIV/AIDS visiting ART Centre IGMC Shimla. Methods: A cross sectional study was conducted among >15 years from September 2016 to August 2017 in ART Centre IGMC Shimla and satisfaction level was assessed by using the PSQ18 instrument. Results: Total 160 participants were enrolled in study among which 71.9% were males while 92.5% were above 30 years of age. Most of the patients were asymptomatic (currently not ill) at the time of consultation and their mode of disease transmission was sexual. The mean scores of PSQ-18 domains i.e. general satisfaction, technical quality, interpersonal manner, communication, financial aspects, time spent with doctor, accessibility and convenience was calculated. Highest score in interpersonal manner, time spent with doctor (3.99±0.12) and lowest score in general satisfaction (3.77±0.54). There was no statistically significant difference between overall satisfaction in relation to different socio demographic and clinical variables found in our study. Conclusions: Our study reflects that patients were much satisfied with the way health care providers were treating them and spent time with them while they were dissatisfied with something about the health care they were receiving.